Pengembangan Model Pembelajaran Jarak Jauh dengan Control Device Memanfaatkan Aplikasi AirDroid - Henny Prasetyani; Desy Nur Cahyani (Jurnal Pendidikan Informatika (EDUMATIC), 2022)
During distance learning, there are problems. Namely, students tend to underestimate when learning occurs because they are bored with online learning and prefer offline learning. This study aims to monitor the activities carried out by students on their smartphones during distance learning so that knowledge is more varied and students are more focused during education. The ADDIE model and development used in this study consisted of the Analysis, Design, Development, Implementation, and Evaluation stages. Data collection techniques use instruments in media and materials; then, the results are analyzed using descriptive statistics. Developing a distance learning model of a control device utilizing the AirDroid application is effective in learning, showing student response results of 88.53%. This is because the AirDroid application has several convenient features that can be implemented during learning. Therefore, the AirDroid application can be used as a distance learning model.